Neighbourhood support and individual and neighbourhood characteristics. Case study in Granada - Palomares-Linares, Isabel; Mesa-Pedrazas, Ángela; Duque-Calvache, Ricardo (Cuadernos de Relaciones Laborales, 2025)
Numerous qualitative studies highlight the importance of neighbourhood support in our lives. However, quantifying these practices is complicated by the lack of specific sources. This article examines how this support is articulated and its relationship with the characteristics of the people and the places where they live, using a survey of the Institute for Regional Development in the metropolitan area of Granada (2008) and logistic regression models. Factors that explain the frequency of interaction and support among neighbours are analysed, as well as the determinants of social isolation and high integration in the neighbourhood. The results show that both individual and neighbourhood variables are significant and contribute differentially to the explanation of these phenomena. In addition, distinct spatial patterns are observed, with working-class areas and municipalities in the metropolitan crown showing greater neighbourhood connectedness than other areas of the capital.